Skepticism in Hume's Politics and Histories - Fosl, Peter S. (Araucaria, 2024)
This essay argues that Hume's political and historical thought is wellread as skeptical and skeptical in a way that roots it deeply in the Hellenistictraditions of both Pyrrhonian and Academical thought. It deploys skepticalinstruments to undermine political rationalism as well as theologically andmetaphysically political ideologies. (1) Hume's is politics of opinion (doxa)and (2) appearance (phainomena). It labors to oppose faction and enthusiasmand generate (3) suspension (epochê), (4) balance (isosthenia), (5) tranquility(ataraxia), and (6) moderation (metriopatheia, moderatio). Because Humeadvocate the use of reflectively generated but epistemically and metaphysicallysuspensive general rules, his political thought is not intrinsically conservative.While it valorizes stability and peace, Humean politics accepts a contested andopen-ended (zetesis) political order, one that requires continuous maintenanceand revision but does not pretend to any ultimate or final progress or end.